Initial experience with the new type A arch dissection stent: restoration of supra-aortic vessel perfusion. (19th May 2021) - Montagner, Matteo; Kofler, Markus; Heck, Roland; Buz, Semih; Starck, Christoph; Kurz, Stephan; Falk, Volkmar; Kempfert, Jörg
Abstract: OBJECTIVES: The goal of the present study is to investigate changes in supra-aortic vessel perfusion after implantation of the non-covered Ascyrus Medical Dissection Stent (AMDS) for surgical treatment of acute type A aortic dissection. METHODS: From 2017 to 2020, 16 consecutive patients treated with AMDS and involvement (dissection to total occlusion) of at least 1 supra-aortic vessel were included in the study. Centre-line based computed tomography measurements of true, false and total lumen area using Terarecon software were performed before and after surgery. Changes in the true lumen area were indexed to the entire vessel area. The paired sample t -test was used to assess the significance of the observed differences. RESULTS: Analysis of supra-aortic vessels and the descending aorta showed significant improvement in true lumen perfusion after the AMDS was implanted. The indexed true lumen area increased postoperatively by 72%, 112% and 30% in the innominate, right and left common carotid arteries, respectively. Total occlusions of both common carotid arteries recovered completely after surgical treatment. The proximal- and the mid-descending aorta showed a 78% and 48% improvement of the indexed true lumen area, respectively. CONCLUSIONS: Arch repair using AMDS shows promising results in the treatment of acute type A aortic dissection. Quantitative measurements of true and false lumen perfusion demonstrated a significant increase in true lumen area and a 100% regression of totally occluded supra-aortic branches. Further examination in a larger cohort of patients and comparison with isolated hemiarch repair are needed to confirm positive vascular remodelling after an AMDS implant.